THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, DISTRIBUTIVE JUSTICE OF PERFORMANCE BENEFITS, AND INTRINSIC MOTIVATION ON JOB SATISFACTION OF STATE CIVIL SERVANT - Aulia Ripda Ramadhaniasari (JCOMENT (Journal of Community Empowerment), 2021)
This study aims to explain the influence of transformational leadership, distributive justice of performance benefits, and intrinsic motivation on job satisfaction in the regional personnel, education and training agency (BKD) Tegal District Government. The object in this study is the head of the agency, the subject in this study is the regional personnel, education and training agency (BKD) employee of the Tegal Regency Government with a minimum period of one year and not a contract employee. This research was conducted with a sample of 52 respondents who have been determined by sampling techniques using non-probability sampling techniques and distributing questionnaires to respondents offline. The analytical tool used by the author is the multiple linear regression analysis techniques with SPSS 25 application program. Based on the results of the analysis, it is found that transformational leadership has a positive effect on job satisfaction, distributive justice benefits have a positive effect on job satisfaction, and intrinsic motivation has a positive effect on job satisfaction.